NAVOIY IS THE FOUNDER OF THE UZBEK LITERARY LANGUAGE (Web of Teachers: Inderscience Research, 2026)
This article examines the pivotal role of Alisher Navoi (1441–1501) in the development and formalization of the Uzbek literary language. By analyzing his major works, specifically Muhokamat al-Lughatayn (The Comparison of the Two Languages), this study explores how Navoi elevated the Chagatai Turkic language to a status equal to that of the esteemed Persian-Tajik literary tradition. The paper highlights his contributions to lexical enrichment, syntactical structure, and the establishment of a formal literary canon that serves as the foundation for modern Uzbek.